O trabalho do enfermeiro: representações sociais de docentes e discentes do curso de graduação em enfermagem - Guidi, Ana Cristina (2009)
This study has been motivated in trying to understand why it is not clear for the nurse the work to carry on and how to develop this process. It is realized in several works that the nurse´s daily routine is followed by no definitions in his/her role, conflicts, disputes and feelings of devalue and invisibility because of the same. This way our objective is to identify, understand, describe and analyze the social representation of the teaching staff and students from Nursing about the work of the nurse. This survey is about a case study in which a methodological theoretical reference has been adopted to the Social Representation Theory proposed by Serge Moscovici. Nursing professors and 8th period students of the Nursing graduation course from an interior Minas Gerais University have been selected. The source used for collecting data was a form that had the technique of free word Association starting from the subjects: Nursing and Being a Nurse; open questions related to the objects of survey and finally a questionnaire aiming to set out people´s profiles. Data has proved that the Nursing profession and the nurse´s work are related to affectionate and attitudinal elements; there is a confusion of the work in Nursing with the nurse´s working process. The pillars that are present in the university and in the representation of professors and students in relation to the nurse´s work is the taking care and managing. Being nuclear care and peripheral managing. We establish that the survey is not explored and valued by the professor and consequently the student leaves university not recognizing him/herself as a knowledge producer and Nursing as a science. In this survey directions, a curricular second thought happens. A study of how this affective abilities are taught, shared, articulated with the scientific knowledge and with the nurse´s work pillars deserve attention, as well as, a look to the subjects and curricular activities from the Nursing course graduation trying to identify how the love that has been nuclear in our study is understood, or be it, what it means, how it is developed, how it is learnt, how it is applied to the daily routine and how it is articulated into the four pillars of the nurse´s work